Assessing coastal erosion risk in a GIS environment - Bio, A. (2016)
Coasts are complex and dynamic zones, susceptible to natural and man-made risk factors and hazards. Impacts will depend on meteo-oceanic conditions (e.g. wave and storm patterns), vulnerability (related with sediments and morphology) and exposure (which depends on coastal orientation and on natural or man-made protective structures). Consequently, even neighbouring beach sectors may show contrasting behaviour because of distinct features. A practical local beach characterization is hence useful for coastal mapping and management. We present procedures for coastal erosion risk assessment in a GIS environment. The effect of exposure on beach dynamics is analysed, considering local characteristics, like shoreline orientation (determined using a poly-line simplification algorithm), beach type and human interventions (determined in-situ), and relating these features to beach dynamics, such as shoreline position, beach area and beach volume determined from successive Digital Elevation Models, using several GIS tools. A case study for the Vila Nova de Gaia coast (Northern Portugal) is presented.